1990
DOI: 10.1139/v90-322
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductance of a mixture of sodium and potassium nitrates in aqueous medium

Abstract: Electrical conductance and density measurements of [xNaNO3 + (1 − x)KNO3] + RH2O system were taken as functions of x, R, and temperature. The mixed alkali effect on molar conductance (Λ) was found to be negligible upto R = 25 and becomes significant in the region where R < 25. It has been shown that for mixed electrolytic system in aqueous medium the concentration range at which the mixed alkali effect on Λ starts becoming significant can be predetermined by plotting the difference in Λ of the two pure elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…4%). Recently, interest has arisen in looking for the MAE in molecular liquid media (8)(9)(10)(11) where no rigid network structure exists and deviations (minima or maxima) in electrical conductivity have been observed. Moynihan (4) suggested that the MAE may only be observed in systems with high viscosity and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…4%). Recently, interest has arisen in looking for the MAE in molecular liquid media (8)(9)(10)(11) where no rigid network structure exists and deviations (minima or maxima) in electrical conductivity have been observed. Moynihan (4) suggested that the MAE may only be observed in systems with high viscosity and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the mixed alkali effect 1-5 (MAE) and its phenomenological influence on the isotherms of dynamic properties (electrical conductivity, viscosity, and diffusion) as functions of composition and temperature in molecular liquid media 6,7 are limited. Recently, the MAE has been investigated using a mixed alkali cation pair in poly-(ethylene oxide) and poly(propylene oxide), which differ from low molar mass solvent systems in the mechanism of cation transport.…”
Section: Introductionmentioning
confidence: 99%